2012
DOI: 10.1111/apa.12035
|View full text |Cite
|
Sign up to set email alerts
|

Endocarditis prophylaxis and congenital heart defects in the Norwegian Public Dental Service

Abstract: There is room for improved education about children with CHD in dentistry and dental education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…On the other hand, Agdestein and his colleagues [20] reported adherence in 68% of cases for urinary tract infections by general practitioners. Moreover, it was also indicated that Norwegian dental service provisions are in accordance to the guidelines [21]. In other studies, however, not only adherence with treatment guidelines but also other simple practices such as the possibility of delaying prescription for infections like otitis [22] and enhanced consultation times with parents in pediatric diagnosis [23] are recommended as strategies to reduce antibiotic consumption and the risk of resistance.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Agdestein and his colleagues [20] reported adherence in 68% of cases for urinary tract infections by general practitioners. Moreover, it was also indicated that Norwegian dental service provisions are in accordance to the guidelines [21]. In other studies, however, not only adherence with treatment guidelines but also other simple practices such as the possibility of delaying prescription for infections like otitis [22] and enhanced consultation times with parents in pediatric diagnosis [23] are recommended as strategies to reduce antibiotic consumption and the risk of resistance.…”
Section: Resultsmentioning
confidence: 99%